2009
DOI: 10.1159/000264938
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Inhibits Adhesion Molecule Expression in TNF-α-Stimulated Human Endothelial Cells via Modulation of the Nuclear Factor ĸB Pathway

Abstract: Background: The isoflavone puerarin is the most abundant isoflavone-C-glucoside extracted from the root (radix puerariae) of the plant Pueraria lobata and possesses many biological activities. In this report, the ability of puerarin to modulate intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1) and endothelial leukocyte adhesion molecule 1 (E-selectin), and to induce changes in the nuclear factor ĸB (NF-ĸB) pathway in human umbilical vein endothelial cells (HUVECs) was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 50 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…ICAM-1 is a multi-functional transmembrane protein, well known for its importance in stabilizing cell-cell interactions, proliferation, and adhesion (Kotteas et al, 2014). Previous studies have indicated that the inhibitory effects of puerarin on ICAM-1 expression were found to not only exist in human umbilical vein endothelial cells (Hu et al, 2010), but also to limit early-stage renal damage in diabetic rats (Pan et al, 2015). The present study showed that PR decreased the levels of ICAM-1 in DMBA-induced breast tumors in rats, an observation supported by the studies described previously.…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 92%
“…ICAM-1 is a multi-functional transmembrane protein, well known for its importance in stabilizing cell-cell interactions, proliferation, and adhesion (Kotteas et al, 2014). Previous studies have indicated that the inhibitory effects of puerarin on ICAM-1 expression were found to not only exist in human umbilical vein endothelial cells (Hu et al, 2010), but also to limit early-stage renal damage in diabetic rats (Pan et al, 2015). The present study showed that PR decreased the levels of ICAM-1 in DMBA-induced breast tumors in rats, an observation supported by the studies described previously.…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 92%
“…Furthermore, TNF-α may stimulate monocytes and macrophages to secrete IL-1, which in turn further induces the production of TNF-α (8). Following excessive TNF-α production in the acute phase of HI/R injury, due to toxic stimulation within the body, IL-1 serves as a pro-inflammatory cytokine that activates various immune and inflammatory cells (9). The levels of IL-1 not only reflect the extent of the inflammatory response, but also direct clinical treatment (9).…”
Section: Introductionmentioning
confidence: 99%
“…Following excessive TNF-α production in the acute phase of HI/R injury, due to toxic stimulation within the body, IL-1 serves as a pro-inflammatory cytokine that activates various immune and inflammatory cells (9). The levels of IL-1 not only reflect the extent of the inflammatory response, but also direct clinical treatment (9). IL-6 is secreted by activated macrophages, lymphocytes and epithelial cells, and may be induced by IL-1β and TNF-α (10).…”
Section: Introductionmentioning
confidence: 99%
“…7 In diet-induced hypercholesterolemic rats, puerarin markedly reduces the total cholesterol by the promotion of cholesterol and bile acid excretion in the liver. 6 Puerarin also improves endothelial function by inhibiting cellular factors, such as adhesive molecules 8 and C-reactive protein, 9 and stimulating endothelial nitric oxide synthase phosphorylation and nitric oxide production via activation of an estrogen receptor-mediated phosphatidylinositol 3-kinase/Akt-and calmodulin-dependent kinase II/AMP-activated protein kinase-dependent pathway. Understanding the metabolic pathway of puerarin will contribute to our understanding of its therapeutic as well as toxic effects.…”
Section: Introductionmentioning
confidence: 99%